Sustainable kidney care delivery and climate change - a call to action - See Cheng Yeo; Xi Yan Ooi; Tracy Suet Mun Tan (BMC, 2022)
Abstract The delivery of kidney care, particularly haemodialysis treatment, can result in substantial environmental impact through greenhouse emissions, natural resources depletion and waste generation. However, strategies exist to mitigate this impact and improve long term environmental sustainability for the provision of haemodialysis treatment. The nephrology community has begun taking actions to improve the environmental sustainability of dialysis, but much work remains to be done by healthcare professionals, dialysis providers and professional organisations.